Court-Ordered Interim Measures in International Arbitration: A Comparative Approach - Bantekas, Ilias (Journal of Law and Commerce, 2023)
This paper argues that there is a distinct cross-border law concerning court-ordered interim measures in aid of international arbitration, which is made up of two key (intertwined) sources, namely: the relevant provisions of the UNCITRAL Model Law on International Commercial Arbitration and supporting case law and legislation in both Model Law states and non-Model Law states. The principles identified in this paper are assumed to qualify as general principles of law. In order for a court at the seat to grant interim relief in international arbitral proceedings the requesting party must demonstrate a prima facie case worthy of consideration, the likelihood of irreparable harm and a balance of inconvenience. There is at present no general consensus as to ex parte interim measures, with many states and national courts showing significant reluctance to grant these on account of the absence of procedural guarantees that they entail. In equal measure, in the absence of bilateral or multilateral treaties that allow national courts to recognize and enforce foreign interim measures in respect of arbitral proceedings seated abroad, states are equally reluctant to allow parties seated in other jurisdictions to approach their courts for interim relief on the ground that the other party has assets or interests there. Although the courts of some powerful nations allow for such requests, there is no general rule in this regard and none is expected in the near future.